Aβ receptors specifically recognize molecular features displayed by fibril ends and neurotoxic oligomers - Ladan Amin (Nature Portfolio, 2021)
PrPC, a receptor for Aβ oligomers, blocks polarized elongation of Aβ fibrils by binding to the rapidly growing end of each fibril. PrPC and other receptors may trap Aβ oligomers and protofibrils on the neuronal surface by binding to a common molecular determinant, initiating a neurotoxic signal.